Plantings with people in mind: increasing use in urban vacant lots through planting design - Sanders, Spencer (Kansas State University, 2020)
Research has shown that frequent contact with nature is beneficial quality of life. Ironically, heavily populated urban environments push nature out of people’s lives yet have many overgrown, poorly perceived vacant lots. This study focuses on how the strategic application of planting design principles in vacant lots can increase use patterns. Study of preferences is based on Rachel and Stephen Kaplan’s Preference Matrix which is used to categorize various planting design principles according to how they affect preference. The study site in northeast Kansas City, Missouri consists of two high-vacancy neighborhoods — Lykins and Sheffield. Residents in these neighborhoods were randomly sampled (n=26) to participate in semi-structured interviews that revealed preferences in planting design. Photographs taken on site were edited using Adobe Photoshop to create scenes that emulate each of the four preference categories. Interview questions asked participants to describe in detail what elements in the photographs are preferable and which are not. These qualitative descriptions were analyzed to reveal what planting design principles were preferred most often. Analysis revealed the most preferred planting design principles and why people preferred them. Analysis also provided clear direction on what category of the Kaplan’s preference matrix is most important to encourage use. Design guidelines were created to inform conceptual vacant lot designs. Subsequent designs were created to showcase preferred planting design principles. Local input improves the quality of outdoor spaces in high vacancy residential areas which can increase how often the designs are used. Planting designs based on community feedback present a simple and elegant solution to some of the problems plaguing high vacancy urban neighborhoods in Kansas City, Missouri.
Keywords: Planting design; Environmental psychology; Preference; Public space